Pharmacist-led adherence support in general practice: a qualitative interview study of adults with asthma - Amy Hai Yan Chan; Robert Horne; Marissa Ayano Mes; Caroline Brigitte Katzer; Vari Wileman; Stephanie Jane Caroline Taylor (BMJ Open)
Objectives The National Health Service (NHS) in England recently introduced general practice pharmacists (GPPs) to provide medication-focused support to both patients and the general practice team. This healthcare model may benefit people with asthma, who currently receive suboptimal care and demonstrate low medication adherence. This study aimed to explore the perspectives of adults with asthma on the potential for pharmacist-led adherence support delivered in general practice, with a focus on how these perspectives are formed.Design and setting The study was conducted in the United Kingdom (UK) utilising a qualitative interview methodology. Participants were invited to partake in a telephone-based semistructured interview, followed by an online questionnaire for demographic details and asthma history. Qualitative data were analysed using thematic analysis.Participants Participants (n=17) were adults with asthma in the UK with a prescription for an inhaled corticosteroid. Participants did not have previous experience with GPPs and were asked to provide their views on a proposed GPP-led service.Results Participant perspectives of GPPs were determined by trust in pharmacists, perceived gaps in asthma care and the perceived strain on the NHS. Trust was based on pharmacists’ perceived clinical competency, established over time, and gauged through a ‘benchmarking’ process. GPP’s fit in current asthma care was assessed based on potential role overlap with other healthcare professionals, continuity of care and medication-related support needs. Participants navigated the NHS based on a perceived hierarchy of healthcare professionals (general practitioners on top, nurses, then pharmacists), and this influenced their perspectives of GPPs.Conclusion While the GPP scheme shows promise based on the perspectives of people with asthma, the identified barriers to optimal patient engagement and service implementation will need to be addressed for the service to be effective.